Performance is Reviewed from Transformational Leadership Style, and Organizational Culture with Work Motivation as an Intervening Variable - Sulistiyantoro, Arif; Mildawani (Jurnal Multidisiplin Madani, 2024)
The study's goal is to identify and assess the impact of transformational leadership style and organizational culture on employee performance using work motivation as an intervening variable at the PT. PNM Banyuwangi Branch. The research design outlines the causal relationship between variables so that hypotheses can be tested quantitatively. The study's population consisted of 82 employees from PT. PNM Banyuwangi Branch. This study used a saturation sampling strategy. Data is collected via a questionnaire. The data from the questionnaire was analyzed using SEM PLS. This study found that transformational leadership style and organizational culture had a direct influence on employee performance. Leadership style and company culture have a direct impact on employee motivation. Transformational Leadership Style Organizational culture has an indirect impact on employee performance through job motivation